What does the Paris Agreement mean for adaptation?. (3rd October 2017) - Lesnikowski, Alexandra; Ford, James; Biesbroek, Robbert; Berrang-Ford, Lea; Maillet, Michelle; Araos, Malcolm; Austin, Stephanie E.
Abstract : The Paris Agreement takes a significant step forward in strengthening the adaptation pillar of global climate policy. By widening the normative framing around adaptation, calling for stronger adaptation commitments from states, being explicit about the multilevel nature of adaptation governance, and outlining stronger transparency mechanisms for assessing adaptation progress, the Agreement is a milestone in ongoing efforts to make adaptation an equal priority with mitigation. Significant work remains to be done, however, to clarify how the long-term goal for adaptation set out in Article 7 will be meaningfully realized. The challenge for Parties in implementing the Paris Agreement will be to establish credible commitments from state and non-state actors with regard to adaptation planning, implementation, and financing. Policy relevance This article provides a critical view on what the Paris Agreement means for the trajectory of adaptation policy at the international and state levels in light of the stated aim of the UN Framework Convention on Climate Change to make adaptation an equal priority with mitigation.